Ratings of activities of daily living in nursing home residents: comparison of self- and proxy ratings with actual performance and the impact of cognitive status - Macháčová, Kateřina; Vaňková, Hana; Holmerová, Iva; Čábelková, Inna; Volicer, Ladislav (European journal of ageing, 2018)
This study was conducted to examine differences between self- and proxy ratings of activities in daily living (ADL) in nursing home residents and to compare them with actual performance. An impact of cognitive status on these ratings was also determined. Data were obtained from 164 dyads of nursing home residents (self-ratings) and their professional care providers (proxy ratings). Statistical procedures included t tests, intraclass correlations, Pearson's correlations, analysis of variance (ANOVA) and ROC curves. Paired t test provided evidence that residents in general overestimated their abilities for all ADLs (p < .01 in all cases), but a substantial subset of 54 residents, with mean MMSE of 18, agreed with their care providers. The mean MMSE score of those who overestimated their abilities was 13 (N = 57). The ANOVA revealed that greater rating differences were associated with more severe cognitive impairment (MMSE, F = 9.93, p < .001). Proxy ratings of walking were not significantly different from actual performances (p = .145), while self-ratings overestimated it (p < .001). Although residents in general overestimated their ADL abilities and results of comparison with actual performance indicated that proxies may be closer to the actual status in this population, a considerable number of those with milder cognitive impairment were able to assess their ADLs with reasonable accuracy.
Keywords: ADL; Self-reports; Proxy reports; Differences; Agreement; Nursing home residents